2016
DOI: 10.1111/jac.12190
|View full text |Cite
|
Sign up to set email alerts
|

Drought Priming at Vegetative Growth Stage Enhances Nitrogen‐Use Efficiency Under Post‐Anthesis Drought and Heat Stress in Wheat

Abstract: To study the effects of early drought priming at 5th‐leaf stage on grain yield and nitrogen‐use efficiency in wheat (Triticum aestivum L.) under post‐anthesis drought and heat stress, wheat plants were first exposed to moderate drought stress (drought priming; that is, the leaf water potential reached ca. −0.9 MPa) at the 5th‐leaf stage for 11 days, and leaf water relations and gas exchange rates, grain yield and yield components, and agronomic nitrogen‐use efficiency (ANUE) of the primed and non‐primed plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 52 publications
2
27
0
1
Order By: Relevance
“…The use of the VSWC is an important tool to monitor water deficit stress in bean plants. It has been considered that a reduction of at least 50% in the values of soil volumetric water content compared with control conditions causes stress levels due to water deficit in wheat plants, which is similar to data obtained in the present study (Liu et al, 2017). In addition, it has been shown that a reduction in the leaf RWC as a consequence of moderate water deficit stress has a significant effect on the physiological parameters of bean plants (Soltys-Kalina et al, 2016), which matches what was found in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The use of the VSWC is an important tool to monitor water deficit stress in bean plants. It has been considered that a reduction of at least 50% in the values of soil volumetric water content compared with control conditions causes stress levels due to water deficit in wheat plants, which is similar to data obtained in the present study (Liu et al, 2017). In addition, it has been shown that a reduction in the leaf RWC as a consequence of moderate water deficit stress has a significant effect on the physiological parameters of bean plants (Soltys-Kalina et al, 2016), which matches what was found in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The season-long abiotic stress treatments that were used in the current study can be considered as abiotic stress priming, and they might have contributed to wheat resilience at the maturity stage. Abiotic stress priming at the vegetative growth stage was suggested as a field management tool to enhance stress tolerance of wheat to multiple abiotic stresses under future stress climates [31].…”
Section: Stress Phasesmentioning
confidence: 99%
“…Larger level of discrimination at FM than RP could be attributed to differences in the sequentially developed yield components, such as tiller [20,69]. The implications of differential plastic responses to the same abiotic stress as a function of growth stage (Figure 2) are of practical significance [31,48]. Reproductive plasticity (e.g., in spike fertility index, spike harvest index and kernels m −2 ) was demonstrated ( Table 2) in response to resource limitations (e.g., caused by SN and SH); however, plasticities of the final reproductive output (i.e., grain yield) and of biomass covaried in T. durum (r = 0.92) and T. aestivum (r = 0.75), but were totally non-overlapping (Figure 3).…”
Section: Growth Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence has shown that an early exposure to a moderate stressor can prepare the plants more quickly or actively to respond to subsequent stress (Bruce et al 2007, Li et al 2015, Liu et al 2017. The trigger for stress tolerance (i.e.…”
mentioning
confidence: 99%